Preparation method of photoelectric tweezers chip and photoelectric tweezers chip

CN122850291BActive Publication Date: 2026-10-30ZHUIGUANG BIOTECHNOLOGY (SHENZHEN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611356836.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-30
Estimated Expiration
2046-09-03

AI Technical Summary

Technical Problem

[0006]本申请提供一种光电镊芯片制备方法及光电镊芯片,用于解决现有技术中微流道与金属电极套刻对准误差大、封装高温损伤光电三极管的问题

Benefits of technology

1、本申请以图案化金属电极层作为背面曝光的内置掩模,使感光性树脂层中的微流道图案与图案化金属电极层实现免套刻自对准,对准偏差绝对值不超过1μm,相较于常规正面套刻工艺,对位精度提升了一个数量级,为后续高精度光电操控奠定了结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122850291B_ABST
    Figure CN122850291B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of semiconductor optoelectronic device manufacturing, and relates to an optoelectronic tweezers chip and a preparation method thereof. The chip comprises an upper plate, a lower plate and a light-cured adhesive layer; the upper plate comprises a transparent substrate, a transparent conductive layer, a patterned metal electrode layer and a dry film microstructure; and the lower plate comprises a phototransistor array. The method comprises the following steps: forming a transparent conductive layer, a patterned metal electrode layer and a photosensitive resin layer on the first surface of the transparent substrate; performing twice exposure and development on the upper plate to form a dry film microstructure; coating a light-cured adhesive composition containing a photo-thermal response component on the surface of the lower plate and aligning and adhering; preliminarily curing by ultraviolet light, exciting the photo-thermal response component by near-infrared light to locally generate heat and assisting complete curing, and realizing low-temperature packaging. According to the application, the overlay deviation is small, the surface temperature of the phototransistor array during the curing process is not higher than 50 DEG C, and the total curing time is not longer than 60 seconds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor optoelectronic device manufacturing technology, and in particular to a method for preparing an optoelectronic tweezers chip and the optoelectronic tweezers chip. Background Technology

[0002] Optoelectronic tweezers technology utilizes the principle of photoinduced dielectrophoresis to achieve non-contact manipulation of micro and nanoparticles. A typical optoelectronic tweezers chip consists of an upper electrode, a lower electrode, and a microchannel between them. The geometric precision of the microchannel and the packaging quality of the upper and lower electrodes directly determine the chip's performance.

[0003] In the fabrication of upper electrode plates, the field has evolved from liquid photoresists to dry film photoresists. Liquid photoresists are formed by spin coating, but they suffer from poor thickness uniformity on large wafers and are prone to air bubble entrapment during the coating process. Dry film photoresists (photosensitive resin laminates) are bonded to the substrate surface in a roll-to-roll manner through heating and pressure. The thickness is guaranteed by the film material itself, and the uniformity and air bubble control are superior to liquid photoresists. However, when dry film is bonded to a substrate with a pre-formed metal electrode pattern, the patterned morphology of the metal electrodes causes air gaps at the dry film bonding interface. More importantly, the metal electrode pattern and the microfluidic channel pattern require two independent photolithography processes, resulting in significant overlay alignment errors between the two processes. In the field of semiconductor active devices, existing technologies disclose the use of back-side exposure self-alignment processes to achieve precise electrode alignment. However, this process is used for active device fabrication, not for the fabrication of microfluidic channels on upper electrode plates of microfluidic chips. The two differ in material systems, development mechanisms, and functional objectives.

[0004] In encapsulation, traditional thermocompression bonding requires high pressure above 150°C. This high temperature causes hydrogen bond breakage in the hydrogenated amorphous silicon of the lower electrode phototransistor, increases defect state density, increases dark current, and reduces photoelectric conversion efficiency. While UV-curable adhesives can avoid high temperatures, conventional UV curing faces three major challenges: UV light decays exponentially within the adhesive layer, resulting in insufficient deep curing; the heat generated during curing is conducted to the phototransistor through the substrate, with local temperatures still reaching 60°C to 80°C; and shadowed areas blocked by metal electrodes cannot receive UV light, forming curing dead zones. In the biomedical field, other studies have introduced photothermal nanoparticles into adhesives to achieve near-infrared photothermal curing, but the adhesive matrix is ​​biological protein rather than UV-curable resin, which differs significantly from chip encapsulation in terms of technical issues, material systems, and curing mechanisms.

[0005] The two process steps mentioned above are treated in isolation in the existing technology, lacking a complete and coordinated solution that can simultaneously solve overlay alignment errors and thermal damage during packaging. Summary of the Invention

[0006] This application provides a method for fabricating an optoelectronic tweezers chip and an optoelectronic tweezers chip, which solves the problems of large alignment errors between microchannels and metal electrodes and damage to phototransistors caused by high temperatures during packaging in the prior art.

[0007] To achieve the above objectives, this application adopts the following technical solution: In a first aspect, this application provides a method for fabricating an optoelectronic tweezers chip, comprising the following steps: S1: A transparent substrate is provided, on the first surface of which a transparent conductive layer and a patterned metal electrode layer are sequentially formed. A photosensitive resin layer is coated on the patterned metal electrode layer and the transparent conductive layer not covered by the patterned metal electrode layer; S2: A first exposure is performed from the second side of the transparent substrate, allowing exposure light to pass through the transparent substrate and the transparent conductive layer and enter the photosensitive resin layer. The patterned metal electrode layer blocks the exposure light to form a first exposure area, causing the photosensitive resin layer to form a first cross-linked area with a corresponding positional relationship to the patterned metal electrode layer. A second exposure is performed from the first side of the transparent substrate through a photomask to form a second cross-linked area. The photosensitive resin layer after the first and second exposures is developed to remove uncross-linked areas, forming a dry film microstructure. S3: Provide a lower electrode plate including a phototransistor array, wherein a photocurable adhesive composition with photothermal response components dispersed on the surface of the lower electrode plate is applied, and a transparent substrate with the dry film microstructure formed thereon is used as an upper electrode plate, which is aligned and bonded to the lower electrode plate, and a photocurable adhesive layer is formed between the upper electrode plate and the lower electrode plate, so that a microchannel is formed between the dry film microstructure and the lower electrode plate; S4: Apply ultraviolet light radiation to initially cure the photocurable adhesive composition that forms the photocurable adhesive layer, and then apply near-infrared light irradiation to excite the photothermal response component in the photocurable adhesive composition to generate heat, assisting in the completion of complete curing, thereby achieving the encapsulation of the upper electrode plate and the lower electrode plate to obtain the photoelectric tweezers chip.

[0008] In one implementation of the first aspect, the photosensitive resin layer is a negative photosensitive resin dry film, which is bonded to the patterned metal electrode layer and the transparent conductive layer not covered by the patterned metal electrode layer by heating and pressurization.

[0009] In one implementation of the first aspect, the thickness of the negative photosensitive resin dry film is 20 μm to 100 μm.

[0010] In one implementation of the first aspect, the absolute value of the overlay alignment deviation between the dry film microstructure and the patterned metal electrode layer does not exceed 1 μm.

[0011] In one implementation of the first aspect, the height of the microchannel is equal to the thickness of the photosensitive resin layer.

[0012] In one implementation of the first aspect, the photothermal response component is selected from at least one of gold nanorods, gold nanoshells, multi-walled carbon nanotubes, and graphene quantum dots.

[0013] In one implementation of the first aspect, the photocurable adhesive composition comprises, by weight: 50 to 70 parts of a UV-curable resin matrix; 15 to 25 parts of an active diluent; 1 to 3 parts of a photoinitiator; and 0.05 to 0.20 parts of a photothermal responsive component.

[0014] In one implementation of the first aspect, the total time for the initial curing and the complete curing does not exceed 60 seconds.

[0015] In one implementation of the first aspect, the photothermal responsive component is dispersed in the photocurable adhesive composition, and the thermal conductivity of the matrix after curing of the photocurable adhesive composition is not greater than 0.5 W / m·K.

[0016] In a second aspect, this application provides an optoelectronic tweezers chip, comprising: an upper electrode plate, including a transparent substrate, a transparent conductive layer located on one side of the transparent substrate, a patterned metal electrode layer located on the side of the transparent conductive layer away from the transparent substrate, and a dry film microstructure self-aligned and connected to the patterned metal electrode layer. The dry film microstructure includes a sidewall that forms a microchannel and an opening region corresponding to the patterned metal electrode layer, wherein at least one edge of the sidewall has a self-aligned positional relationship with the corresponding edge of the patterned metal electrode layer. A lower electrode plate is located on one side of the upper electrode plate, and the lower electrode plate includes a phototransistor array; and a photocurable adhesive layer is sandwiched between the upper electrode plate and the lower electrode plate, the photocurable adhesive layer being formed by curing a photocurable adhesive composition dispersing photothermal responsive components; The dry film microstructure and the lower electrode plate form a microchannel for the passage of microfluidic fluid, and the microchannel is connected to the surface of the patterned metal electrode layer through the opening region.

[0017] The technical solution provided in this application can achieve the following beneficial effects: 1. This application uses a patterned metal electrode layer as an embedded mask for back exposure, enabling the microchannel pattern in the photosensitive resin layer to achieve self-alignment with the patterned metal electrode layer without overlay. The absolute value of the alignment deviation does not exceed 1μm. Compared with the conventional front overlay process, the alignment accuracy is improved by an order of magnitude, laying a structural foundation for subsequent high-precision photoelectric control.

[0018] 2. This application provides a precise alignment basis for packaging through self-alignment process, and provides a thermal protection barrier for the self-alignment results through low temperature packaging, which ensures a high-precision correspondence between the microchannel position, the metal electrode position and the packaging thickness, effectively avoiding the problem of uneven electric field distribution caused by the deviation of the upper and lower electrode spacing, and ensuring the photoelectric control accuracy.

[0019] 3. This application employs a dual curing mechanism of initial UV curing and near-infrared photothermal assisted curing, significantly improving encapsulation efficiency and reducing the risk of thermal damage: the total curing time does not exceed 60 seconds, a substantial reduction compared to conventional UV curing; the photothermal responsive components generate localized heat only within the nanoscale range inside the adhesive layer under near-infrared light irradiation, and the low thermal conductivity of the cured substrate blocks heat conduction, preventing heat from being conducted outward through the substrate. During the curing process, the surface temperature of the phototransistor array on the lower electrode does not exceed 50°C, eliminating the dry film softening deformation and thermal expansion mismatch caused by the cumulative thermal effects of traditional high-temperature hot-press bonding and conventional UV curing, and effectively protecting the heat-sensitive devices such as the phototransistor on the lower electrode. Attached Figure Description

[0020] The exemplary embodiments of this application can be more fully understood by referring to the following accompanying drawings. The drawings are provided to further illustrate the embodiments of this application and form part of the specification. They are used together with the embodiments of this application to explain this application and do not constitute a limitation thereof. In the drawings, the same reference numerals generally represent the same components or steps.

[0021] Figure 1 This is a process flow diagram of the photoelectric tweezers chip fabrication method provided in the embodiments of this application; Figure 2 This is a schematic diagram of the cross-sectional structure of the upper electrode plate in the optoelectronic tweezers chip provided in the embodiments of this application; Figure 3 This is a schematic diagram of the cross-sectional structure of the photoelectric tweezers chip after the first exposure, provided in an embodiment of this application. Figure 4 This is a schematic cross-sectional view of the dry film microstructure provided in the embodiments of this application; Figure 5 This is a schematic diagram of the cross-sectional structure of the optoelectronic tweezers chip provided in the embodiments of this application.

[0022] Figure Labels 1—Transparent substrate; 2—Transparent conductive layer; 3—Patterned metal electrode layer; 4—Photosensitive resin layer; 41—First cross-linking region; 42—Second cross-linking region; 5—Microchannel; 6—Photocurable adhesive layer; 7—Lower electrode plate. Detailed Implementation

[0023] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that, unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps set forth in these embodiments do not limit the scope of the present application.

[0024] Those skilled in the art will understand that the terms "first," "second," etc., in the embodiments of this application are only used to distinguish different steps, devices, or modules, and do not represent any specific technical meaning, nor do they indicate a necessary logical order between them. It should also be understood that in the embodiments of this application, "multiple" can refer to two or more, and "at least one" can refer to one, two, or more. Furthermore, the term "and / or" in this application is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone.

[0025] In the description of this application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0026] In the description of this application, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "setting," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. In the description of the embodiments of this application, unless otherwise stated, " / " means "or," for example, A / B can mean A or B.

[0027] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the term "transparent substrate" refers to a flat material that can transmit ultraviolet and near-infrared light for exposure, and may be borosilicate glass, quartz or transparent polymer substrate.

[0028] The term "transparent conductive layer" refers to a thin film that is both conductive and has high optical transmittance in the visible to near-ultraviolet range. In this application, an indium tin oxide (ITO) thin film with a thickness of 100 nm to 1000 nm is used.

[0029] The term "patterned metal electrode layer" refers to a patterned structure formed by photolithography after a conductive metal layer deposited on a transparent conductive layer is etched. This patterned structure serves as an electrode array to conduct electrical signals when the optoelectronic tweezers chip is working, and as an optical mask for back-side exposure in the fabrication process.

[0030] The term "photosensitive resin layer" refers to a photosensitive resin laminate, commonly known in the industry as dry film photoresist. It is bonded to the substrate surface by heating and pressurizing, without the need for liquid coating or pre-baking. After exposure and development, the photosensitive resin layer forms a microchannel microstructure.

[0031] The term "first exposure" refers to applying irradiation from the uncoated side (second side) of a transparent substrate. The irradiated light passes through the transparent substrate and the transparent conductive layer, and is blocked by the patterned metal electrode layer on the first side. This creates a cross-linked region in the photosensitive resin layer that is precisely aligned with the patterned metal electrode layer, using the pattern of the patterned metal electrode layer as an internal optical mask. The cross-linked region formed in the photosensitive resin layer during the first exposure is called the "first cross-linked region".

[0032] The term "second exposure" refers to the process of applying irradiation through an external photomask to the first side (coated side) of a transparent substrate, forming a cross-linked region in the photosensitive resin layer that corresponds to the microchannel pattern. This region is called the "second cross-linked region".

[0033] The term "differential double-sided exposure" refers to an exposure method in which the first and second exposures use different wavelengths and are incident from the second and first sides of a transparent substrate, respectively, so that the photosensitive resin layer forms cross-linked regions on the side closer to the transparent substrate and the side farther away from the transparent substrate.

[0034] The term "dry film microstructure" refers to the microstructure formed in a photosensitive resin layer after the first exposure, the second exposure, and development, which includes self-aligned openings and self-aligned sidewalls.

[0035] The term "self-aligned opening" refers to the opening region formed after the photosensitive resin layer located directly above the patterned metal electrode layer is removed after development, which is self-aligned with the patterned metal electrode layer.

[0036] The term "self-aligned connection" refers to the alignment relationship in which the sidewall edge of the dry film microstructure and the corresponding edge of the patterned metal electrode layer are naturally inherited in position and can be achieved without additional overlay alignment steps. The alignment deviation is determined by the light-shielding boundary accuracy of the patterned metal electrode layer in the first exposure.

[0037] The term "self-aligned sidewall" refers to the sidewall structure formed by the photosensitive resin layer located directly above the gap of the patterned metal electrode layer after development, which is self-aligned with the edge of the patterned metal electrode layer.

[0038] The term "phototransistor array" refers to a photosensitive structure formed by arranging multiple phototransistors in an array, used to generate photogenerated carriers under illumination to form a dielectric electrophoretic control electric field.

[0039] The term "microchannel" refers to a fluid channel cavity formed by the dry film microstructure and the lower electrode, through which microfluidic fluid can pass. Its cross-sectional geometry is determined by the developing process and the exposure pattern.

[0040] The term "microfluidic pattern" refers to the geometric pattern used to define the liquid flow path in an optoelectronic tweezer chip, including linear, serpentine, bifurcated, or array-shaped channel topologies.

[0041] The term "photothermal responsive component" refers to a material that absorbs photon energy in the near-infrared band (780 nm to 1064 nm) and converts it into heat energy through non-radiative relaxation. Its form includes one or more of nanoparticles, nanosheets, nanotubes, quantum dots, or conductive polymers. Photothermal conversion efficiency is related to the size, shape, and type of material.

[0042] The term "photocurable adhesive composition" refers to a mixed system containing a photocurable resin matrix, a photoinitiator, and a photothermal responsive component, which undergoes a free radical polymerization reaction under ultraviolet light to cure, while the photothermal responsive component generates local heat under near-infrared light to accelerate the curing reaction.

[0043] The term "photocurable adhesive layer" refers to the adhesive layer sandwiched between the upper and lower electrodes, formed after a photocurable adhesive composition containing photothermal responsive components is initially cured by ultraviolet light and then fully cured with near-infrared photothermal assistance.

[0044] Furthermore, it should be understood that, for ease of description, the dimensions of the various parts shown in the accompanying drawings are not drawn to actual scale. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its application or use. Techniques, methods, and devices known to those skilled in the art will not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. It should be noted that similar reference numerals and letters in the following drawings denote similar items; therefore, once an item is defined in one drawing, it need not be further discussed in subsequent drawings.

[0045] Furthermore, the technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.

[0046] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0047] The technical solutions provided in the embodiments of this application will be described below with reference to the accompanying drawings.

[0048] See Figures 1 to 5 This embodiment provides a method for fabricating an optoelectronic tweezers chip, including the following steps S1 to S4.

[0049] S1: Upper electrode substrate preparation: A 4-inch borosilicate glass wafer was used as the transparent substrate 1, with a thickness of 0.7 mm. This material has a transmittance of over 90% in the 365 nm to 1064 nm wavelength range, meeting the optical requirements for back-side exposure and near-infrared curing. An ITO thin film was deposited on the first side of the wafer as a transparent conductive layer 2 with a thickness of 200 nm by magnetron sputtering. The measured sheet resistance of the ITO film was 15 Ω, and the measured transmittance in the 365 nm wavelength range was 85%, which meets the conductivity requirements and allows ultraviolet light from the back-side exposure to pass through. The reason for choosing a thickness of 200 nm is that the optical transmittance of the ITO film decreases with increasing thickness, the sheet resistance decreases with increasing thickness, and the internal stress of the film increases with increasing thickness. 200 nm is the balance point between transmittance (85% in the 365 nm wavelength range), sheet resistance (15 Ω), and the mechanical stability of the film.

[0050] Subsequently, a metal electrode layer is deposited on the ITO thin film via electron beam evaporation, preferably using Au / Ti materials. The Ti layer is 20 nm thick as an adhesion layer, and the Au layer is 200 nm thick as the electrode substrate. Au was chosen as the electrode material because: Au has an optical reflectivity of 36% at 365 nm, effectively blocking ultraviolet light from the back side exposure, thus acting as a mask; Au also has good chemical stability, making it less susceptible to corrosion during subsequent wet etching and cleaning processes. Furthermore, the optical density of the Au layer at this thickness is sufficient to reduce the transmittance of 365 nm ultraviolet light to near zero, ensuring that the patterned metal electrode layer completely shields the back side from exposure; and at this thickness, the linewidth loss at the wet etching edge is controllable, and the internal stress of the film layer does not cause substrate warping.

[0051] The Au / Ti layer was patterned using positive photoresist photolithography and wet etching with potassium iodide / iodine (KI / I2) solution to form a patterned metal electrode layer 3, including an interdigitated electrode array and peripheral leads. After removing the photoresist, the layer was ultrasonically cleaned for 5 minutes each with acetone, isopropanol, and deionized water, and then dried with nitrogen.

[0052] See also Figure 2 A commercially available negative dry film photoresist, 30 μm thick, is laminated onto the wafer surface covered by the patterned metal electrode layer 3 and the transparent conductive layer not covered by the patterned metal electrode layer 3 to form a photosensitive resin layer 4. The lamination conditions are: temperature 85℃, pressure 0.3 MPa, and lamination speed 0.5 m / min. This temperature softens the protective film (PET carrier) of the dry film, allowing the resin layer to flow and fill the gaps between the patterned metal electrode layer under pressure, while preventing premature photocrosslinking of the photosensitive resin. Before lamination, the dry film is pre-cut to cover the effective area of ​​the wafer with a 5 mm edge allowance. Lamination is performed in a vacuum laminator at a vacuum level below -0.08 MPa to eliminate air bubbles at the lamination interface.

[0053] S2: Dry film microstructure formation: See [link] Figure 3 The first exposure is performed on the second side of the wafer. The exposure light source is ultraviolet light with a center wavelength of 365 nm, and the exposure dose is 150 mJ / cm². Under the exposure dose conditions of this embodiment, 365 nm exposure can enable the photosensitive resin layer 4 to reach a predetermined degree of crosslinking on the side near the transparent substrate 1 without producing a significant proximity effect. The optical path of the first exposure is as follows: ultraviolet light passes through the transparent substrate 1 and the transparent conductive layer 2, and is blocked by the patterned metal electrode layer 3. The photosensitive resin layer region located directly above the gap of the patterned metal electrode layer 3 receives ultraviolet light irradiation and undergoes a photocrosslinking reaction on the side near the transparent substrate 1, forming a first crosslinking region 41. Since the penetration depth of 365 nm ultraviolet light in the photosensitive resin layer is limited, the side of the region directly above the gap away from the transparent substrate 1 is not yet crosslinked. The photosensitive resin layer region located directly above the patterned metal electrode layer 3 is blocked by the metal electrode and is in the shadow, so no photocrosslinking reaction occurs. The reason for choosing a wavelength of 365nm is that the photosensitive peak of this negative dry film photoresist is located in the range of 350nm to 370nm, and 365nm is at the center of the photosensitive peak, resulting in the highest photochemical reaction efficiency. At the same time, the transmittance of 365nm ultraviolet light is high enough for 0.7mm borosilicate glass and 200nm ITO (overall transmittance of 76%), ensuring that the light dose reaching the photosensitive resin layer meets the crosslinking threshold.

[0054] Then, a second exposure is performed on the first surface of the transparent substrate 1 through an external photomask. The external photomask is a dark field mask, in which the microchannel pattern area is light-blocked and the area outside the pattern is light-transmitting. The microchannel pattern area corresponds to the area directly above the patterned metal electrode layer 3, ensuring that this area remains uncrosslinked in both exposures. The exposure wavelength is 405 nm, and the exposure dose is 180 mJ / cm². 405 nm is in the long-wavelength region where the dry film photosensitivity is relatively low, so the dose is slightly higher than the 365 nm exposure dose to compensate for the sensitivity difference. The penetration depth of 405 nm light is greater than that of 365 nm, enabling the photosensitive resin layer on the side away from the transparent substrate 1 to obtain a depth distribution matching that of the first exposure. The photosensitive resin layer located directly above the gap of the patterned metal electrode layer 3 is crosslinked on the side away from the transparent substrate 1 in this exposure, connecting with the first crosslinked area 41 along the thickness direction of the photosensitive resin layer, together forming a full-thickness crosslinked support pillar. In addition, the light-transmitting area of ​​the external photomask also crosslinks the photosensitive resin layer at other locations. The cross-linked regions formed in the photosensitive resin layer during the second exposure are collectively referred to as the second cross-linked regions 42, thus forming differential double-sided exposure. A microchannel pattern is etched on the photomask, and coarse alignment is performed with the patterned metal electrode layer on the wafer using optical alignment marks. Since the width of the microchannel is much larger than the coarse alignment error of the second exposure, the second exposure only needs to define the macroscopic boundaries, orientation, and branch topology of the microchannel, without requiring precise overlay with the patterned metal electrode layer; the precise position and width of the opening region and support pillars are determined by the self-alignment of the first exposure using the patterned metal electrode layer as an internal mask.

[0055] Finally, development was performed in a 1% sodium carbonate (Na₂CO₃) aqueous solution at 30°C for 120 seconds. During development, the photosensitive resin in the uncrosslinked areas was dissolved and removed by the alkali solution, while the crosslinked areas, due to photocrosslinking, remained insoluble in the alkali solution and formed the dry film microstructure. After development, an upper electrode plate with self-aligned microchannels was obtained. Because the dry film area directly above the patterned metal electrode layer was not exposed to light and was removed during development, the metal electrode surface was exposed and connected to the microchannels; while the dry film area directly above the gap between the metal electrodes was retained due to photocrosslinking, forming self-aligned sidewalls. The microchannel width was 200 μm, the depth was 30 μm (equal to the dry film thickness), and the sidewall angle was 86°. Measurements using optical microscopy and scanning electron microscopy (SEM) showed that the alignment deviation between the edge of the dry film microstructure and the edge of the patterned metal electrode layer was less than 0.5 μm. The positional relationship of the dry film microstructure retained after development is determined by the light-shielding boundary of the patterned metal electrode layer during the first exposure, thereby achieving self-alignment of the microchannel and the metal electrode without overlay.

[0056] S3: Coating and Bonding of the UV-curable Adhesive Composition: First, prepare the UV-curable adhesive composition according to the following parts by weight: 60 parts of commercially available bisphenol A type epoxy acrylate UV-curable resin. This resin was chosen because it has high crosslinking density and excellent chemical resistance after curing, meeting the sealing requirements for long-term use of microfluidic chips. 20 parts of triethylene glycol dimethacrylate (TEGDMA) were used as an reactive diluent to adjust the viscosity. 2 parts of commercially available bis(phosphine oxide) photoinitiator were added. This photoinitiator has strong absorption in the 365nm to 405nm wavelength range, high initiation efficiency, and the photolysis products are colorless and do not affect the optical transparency of the adhesive layer. 0.1 parts of gold nanorods were added. The aspect ratio of the gold nanorods was 3:1, and the longitudinal plasmon absorption peak was at 808nm. The reason for choosing gold nanorods instead of gold nanospheres is that the surface plasmon absorption peak of gold nanospheres is around 520 nm (visible light region), which overlaps with the UV curing band and interferes with the absorption of the photoinitiator. The longitudinal absorption peak of gold nanorods can be tuned to the near-infrared region (780 nm to 980 nm) by adjusting the aspect ratio, completely separating it from the UV curing band (365 nm), thus achieving independent control of UV curing and NIR photothermal effect. 0.05 parts of stabilizer (hydroquinone) are added to prevent self-polymerization of the composition during storage. The gold nanorods are first dispersed in a small amount of dichloromethane and sonicated for 30 minutes to ensure uniform dispersion. Then, they are mixed with the UV resin matrix and reactive diluent, stirred at 40°C for 2 hours to allow the solvent to evaporate, and finally, the photoinitiator and stabilizer are added, followed by vacuum degassing for 30 minutes.

[0057] Then, see Figure 5 A prepared photocurable adhesive composition 6 is applied along the isolation wall trajectory on the surface of the phototransistor array on the lower electrode plate 7. A pneumatic dispensing machine is used, with an adhesive line width of 200 μm and a line height of 50 μm. The dispensing path follows the isolation wall of the lower electrode plate, avoiding the active region of the phototransistor. A custom alignment fixture is used to align and bond the upper and lower electrodes. The pressing force is 0.1 MPa, lasting for 30 seconds. During the pressing process, the adhesive composition flows under pressure to fill the gap between the upper and lower electrodes, forming a uniform adhesive layer.

[0058] S4: Dual-curing chip encapsulation: First, ultraviolet light is applied from the transparent upper electrode side. The light source is a 365nm LED array with an intensity of 50mW / cm² and an irradiation time of 15 seconds. The ultraviolet light passes through the transparent substrate 1 and the transparent conductive layer 2, reaching the photocurable adhesive composition, exciting the photoinitiator to generate free radicals, and initiating the chain polymerization reaction of the acrylate resin, so that the surface and shallow layer of the adhesive layer are initially cured and shaped.

[0059] Subsequently, near-infrared light was applied, with the light source being an 808nm laser diode array, a power density of 1W / cm², and an irradiation time of 30 seconds. The near-infrared light passed through the transparent substrate and the transparent conductive layer, reaching the gold nanorods in the photocurable adhesive layer 6. The gold nanorods underwent longitudinal localized surface plasmon resonance at 808nm, converting the absorbed light energy into heat energy through non-radiative relaxation, generating localized high temperatures in the nanoscale range around the gold nanorods.

[0060] This localized high temperature has a triple effect: First, it accelerates the thermal decomposition of the photoinitiator, generating free radicals in the deep layers of the adhesive and in the UV-shadowed areas (areas blocked by metal electrodes), eliminating curing dead zones; second, it enhances the mobility of resin segments, promotes the formation of cross-linked networks, and improves the degree of curing; third, the heat is concentrated in the nanoscale range around the gold nanorods, forming a thermal barrier through the low thermal conductivity (0.5 W / m·K) of the resin matrix, preventing heat transfer to the phototransistor through the substrate. Tests showed that when the thermal conductivity of the matrix after curing is in the range of 0.2~0.5 W / (m·K), localized thermal barrier within the adhesive layer can be achieved, keeping the surface temperature of the phototransistor array below 50°C. Real-time monitoring with an infrared thermal imager showed that the highest surface temperature of the phototransistor array in the lower electrode 7 during curing was 42.3°C. In contrast, using a conventional UV adhesive (without gold nanorods, the same resin system) resulted in a phototransistor surface temperature of 65.2°C after 120 seconds of UV curing.

[0061] Finally, the appearance and bonding strength of the cured chip were inspected. The bond shear strength was tested using a push-pull testing machine and found to be 5.38 MPa. The performance of the phototransistor was tested using dark current as an indicator; the change in dark current before and after curing was 2.6%, meaning a performance retention rate of 97.4%. The total curing time (time used for the dual-curing encapsulation steps) was 44.6 seconds.

[0062] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0063] Example 2 The difference between this embodiment and embodiment 1 is that different wavelengths are used for double-sided exposure in S2, which is an alternative implementation method in which different wavelengths are used for the first exposure and the second exposure.

[0064] In the first exposure of S2, this embodiment uses a wavelength of 405 nm and an exposure dose of 180 mJ / cm². Compared to 365 nm, 405 nm provides a greater effective exposure depth in this photosensitive resin system. Therefore, the first exposure at 405 nm allows for more complete photocrosslinking in the bottom region of the photosensitive resin layer (near the transparent substrate).

[0065] In the second exposure of S2, the wavelength is still 365nm, and the exposure dose is 150mJ / cm². The shallow penetration depth and high surface resolution of 365nm light enable precise pattern definition in the top region of the photosensitive resin layer (near the air side).

[0066] After differential double-sided exposure, the sidewall angle of the microchannels obtained by development increased from 86° in Example 1 to 88°, and the resolution of both the bottom and top was improved. The remaining steps were the same as in Example 1.

[0067] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0068] Example 3 The difference between this embodiment and Embodiment 1 lies in the types of photothermal response components in S3 and the near-infrared light parameters in S4.

[0069] In S3, gold nanorods were replaced with multi-walled carbon nanotubes with diameters ranging from 10 nm to 20 nm and lengths from 1 μm to 5 μm, at an addition amount of 0.05 parts. Multi-walled carbon nanotubes exhibit photothermal conversion capabilities in a broad wavelength range from 808 nm to 1064 nm, with the absorption mechanism being a broadband absorption without interband transitions.

[0070] In S4, the near-infrared wavelength was changed to 1064 nm, the power density was 0.8 W / cm², and the irradiation time was 45 seconds. The photothermal conversion efficiency of multi-walled carbon nanotubes at 1064 nm is lower than that of gold nanorods at 808 nm (the LSPR enhancement effect of gold nanorods makes the photothermal efficiency 2 to 3 times that of multi-walled carbon nanotubes), so the irradiation time needs to be appropriately extended.

[0071] During the curing process, the surface temperature of the phototransistor was 44.8℃, and the bonding shear strength was 3.21 MPa. The remaining steps were the same as in Example 1.

[0072] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0073] Example 4 The difference between this embodiment and Embodiment 1 lies in the types of photothermal response components in S3 and the near-infrared light parameters in S4.

[0074] In S3, gold nanorods were replaced with gold nanoshells, which consist of a silica core and a gold shell, with an outer diameter of 120 nm and a gold shell thickness of 15 nm. The longitudinal localized surface plasmon resonance absorption peak is located at 800 nm, and the addition amount is 0.1 parts. The reason for choosing gold nanoshells is that their shell thickness can be independently controlled, so that the longitudinal absorption peak is stably located in the 780 nm to 900 nm near-infrared window, which is fully separated from the ultraviolet curing band (365 nm) and avoids competition with the photoinitiator absorption.

[0075] In S4, the near-infrared wavelength was 808 nm, the power density was 0.9 W / cm², and the irradiation time was 35 seconds. The photothermal conversion efficiency of the gold nanoshells at 808 nm was comparable to that of the gold nanorods, both belonging to the noble metal plasmon resonance mechanism.

[0076] During the curing process, the surface temperature of the phototransistor was 44.1℃, the bond shear strength was 4.26MPa, and the performance retention rate was 95.1%. The remaining steps were the same as in Example 1.

[0077] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0078] Example 5 The difference between this embodiment and Embodiment 1 lies in the types of photothermal response components in S3 and the near-infrared light parameters in S4.

[0079] In S3, gold nanorods were replaced with graphene quantum dots with a particle size of 5 nm to 10 nm. These quantum dots exhibit absorption in a wide near-infrared band (900 nm to 1100 nm), with a peak at 1064 nm, and are added at an amount of 0.15 parts. The reason for choosing graphene quantum dots is that they have low preparation costs, and the near-infrared absorption can be tunable over a wide range through size and surface modification.

[0080] In S4, the near-infrared light wavelength was 1064 nm, the power density was 0.7 W / cm², and the irradiation time was 40 seconds. During the curing process, the surface temperature of the phototransistor was 47.8 °C, the bond shear strength was 3.67 MPa, and the performance retention rate was 93.2%. The remaining steps were the same as in Example 1.

[0081] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0082] Example 6 The difference between this embodiment and Embodiment 1 is that the thickness of the photosensitive resin layer and the width of the microchannel are different in S2, which is used to verify the repeatability and universality of the self-alignment process of this application under different geometric dimensions.

[0083] In S1, a commercially available negative dry film photoresist with a thickness of 50 μm was used, and the bonding conditions were the same as in Example 1. The first exposure wavelength was 365 nm, and the exposure dose was increased to 160 mJ / cm² (due to the increased dry film thickness, the dose needed to ensure full-thickness crosslinking in the gap region); the second exposure wavelength was 405 nm, and the exposure dose was increased to 200 mJ / cm². The width of the microchannel pattern on the photomask was 300 μm.

[0084] The upper electrode obtained after development has a microchannel width of 300 μm, a depth of 50 μm (equal to the dry film thickness), and a sidewall angle of 86°. Measurements using optical microscopy and scanning electron microscopy (SEM) showed that the alignment deviation between the edge of the dry film microstructure and the edge of the patterned metal electrode layer did not exceed 0.8 μm, which is still much smaller than the 3 μm to 5 μm deviation of conventional front-side overlay processes, verifying the repeatability and universality of the self-alignment process under different channel sizes. The remaining steps are the same as in Example 1.

[0085] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0086] Comparative Example 1 The upper electrode plate is fabricated using a conventional front-side exposure overlay process. This means that the first exposure in step 2 is omitted; instead, two independent front-side exposures are performed using the front-side alignment mark to form the metal electrode pattern and the microfluidic channel pattern, respectively. The remaining processes are the same as in Example 1.

[0087] According to optical microscopy measurements, the alignment accuracy is 3.8μm. Due to overlay error, the microchannels of some chips deviate from the center of the metal electrode, and the active area deviation rate is 15% (that is, 15% of the chips fail to meet the performance standards due to poor alignment).

[0088] The alignment deviation data of Examples 1, 6, and Comparative Example 1 under varying dry film thickness and microchannel width are summarized in Table 1 below: Table 1 Dry film thickness 30μm 50μm 30μm Microchannel width 200μm 300μm 200μm Alignment deviation ≤0.5μm ≤0.8μm 3.8μm As can be seen from Table 1, when the dry film thickness increases from 30 μm to 50 μm and the microchannel width increases from 200 μm to 300 μm, the self-alignment process of this application can still control the alignment deviation within the submicron range (not exceeding 0.8 μm), proving that the process has good repeatability and dimensional universality; while the alignment deviation of Comparative Example 1 is still ±3 μm to ±5 μm under the same conditions, further demonstrating the significant advantages of the self-alignment process compared with the conventional overlay process.

[0089] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0090] Comparative Example 2 A conventional UV-curable adhesive without gold nanorods was used (same resin matrix and photoinitiator ratio as in Example 1, but without gold nanorods). In step 4, the UV curing time was extended to 120 seconds, and near-infrared irradiation was not performed. The remaining processes were the same as in Example 1.

[0091] After curing, infrared thermal imaging showed that the surface temperature of the phototransistor rose to 65.2℃ (the cumulative thermal effect of 120 seconds of UV LED irradiation caused the substrate to heat up). The phototransistor's performance was tested using dark current as an indicator, and the performance retention rate was 82.1% (the reason for the 17.9% performance decrease is analyzed as follows: 65...). ° Temperature C causes some weak Si-H bonds in hydrogenated amorphous silicon to break, increasing the defect state density.

[0092] It should be understood that the sequence number of each step in the above embodiments does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0093] By employing a first-exposure self-alignment process, the alignment accuracy of the dry film microchannels and patterned metal electrode layers is improved by an order of magnitude, decreasing from 3-5 μm to less than 1 μm. Through a dual photothermal curing mechanism—namely, the synergistic effect of UV light initial curing and near-infrared light excitation of photothermal response components generating localized heat—the curing time is shortened from 120 seconds to less than 60 seconds. Simultaneously, the surface temperature of the phototransistor is reduced from 65.2℃ to 42.3℃, and the performance retention rate is increased from 82.1% to 97.4%.

[0094] The photothermal dual curing mechanism adopted in this application avoids the above constraints in the following ways: ultraviolet light initially cures the surface and shallow layer of the adhesive layer at room temperature, and the free radical polymerization of the photoinitiator does not produce a macroscopic temperature rise, so it can be immediately shaped after pressing and maintain the uniformity of the adhesive layer thickness; near-infrared light excites the photothermal response components to generate heat only in the nanoscale range inside the adhesive layer, and the thermal barrier effect of the matrix thermal conductivity of no more than 0.5 W / m·K prevents heat from being conducted across the adhesive layer-dry film interface.

[0095] Therefore, this application does not simply employ back-side exposure technology, but rather utilizes the pre-formed patterned metal electrode layer as an exposure mask, allowing the microchannel microstructure to naturally inherit the positional relationship of the electrode pattern during its formation. Combined with low-temperature dual-curing encapsulation, this positional relationship is maintained during the encapsulation process, thus forming a self-aligned manufacturing process throughout the entire manufacturing process. This process eliminates the conventional overlay alignment step at its source and transforms the encapsulation stage from a factor that degrades precision to a factor that maintains precision. This is the substantial improvement of this application, distinguishing it from a simple superposition of self-aligned technology and low-temperature encapsulation technology.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application.

Claims

1. A method for fabricating an optoelectronic tweezers chip, characterized in that, Includes the following steps: S1: Provide a transparent substrate, wherein a transparent conductive layer and a patterned metal electrode layer are sequentially formed on the first surface of the transparent substrate, and a photosensitive resin layer is coated on the patterned metal electrode layer and the transparent conductive layer not covered by the patterned metal electrode layer. S2: The second side of the transparent substrate is exposed for the first time. The exposure light passes through the transparent substrate and the transparent conductive layer and is incident on the photosensitive resin layer. The patterned metal electrode layer blocks the exposure light to form the first exposure area. The photosensitive resin layer forms a first cross-linked area with a corresponding positional relationship to the patterned metal electrode layer. The first side of the transparent substrate is exposed for the second time through a photomask to form a second cross-linked area. The photosensitive resin layer after the first exposure and the second exposure is developed to remove the uncross-linked areas and form a dry film microstructure. S3: Provide a lower electrode plate including a phototransistor array, wherein a photocurable adhesive composition with photothermal responsive components dispersed on the surface of the lower electrode plate is coated, and the transparent substrate is used as an upper electrode plate and aligned and bonded with the lower electrode plate, and a photocurable adhesive layer is formed between the upper electrode plate and the lower electrode plate, so that a microchannel is formed between the dry film microstructure and the lower electrode plate; S4: Apply ultraviolet light radiation to initially cure the photocurable adhesive composition, and then apply near-infrared light irradiation to excite the photothermal response component to generate heat, assisting in the complete curing, thereby achieving the encapsulation of the upper electrode plate and the lower electrode plate, and obtaining an optoelectronic tweezers chip; The photocurable adhesive composition comprises, by weight, 50 to 70 parts of UV-curable resin matrix; 15 to 25 parts of reactive diluent; 1 to 3 parts of photoinitiator; and 0.05 to 0.20 parts of photothermal responsive component.

2. The method for fabricating an optoelectronic tweezers chip according to claim 1, characterized in that, The photosensitive resin layer is a negative photosensitive resin dry film, which is bonded to the patterned metal electrode layer and the transparent conductive layer not covered by the patterned metal electrode layer by heating and pressurization.

3. The method for fabricating an optoelectronic tweezers chip according to claim 2, characterized in that, The thickness of the negative photosensitive resin dry film is 20 μm to 100 μm.

4. The method for fabricating an optoelectronic tweezers chip according to claim 1, characterized in that, The absolute value of the overlay alignment deviation between the dry film microstructure and the patterned metal electrode layer does not exceed 1 μm.

5. The method for fabricating an optoelectronic tweezers chip according to claim 1, characterized in that, The height of the microchannel is equal to the thickness of the photosensitive resin layer.

6. The method for fabricating an optoelectronic tweezers chip according to claim 1, characterized in that, The photothermal response component is selected from at least one of gold nanorods, gold nanoshells, multi-walled carbon nanotubes, and graphene quantum dots.

7. The method for fabricating an optoelectronic tweezers chip according to claim 1, characterized in that, The total time for initial curing and complete curing shall not exceed 60 seconds.

8. The method for fabricating an optoelectronic tweezers chip according to claim 5, characterized in that, The photothermal responsive component is dispersed in the photocurable adhesive composition, and the thermal conductivity of the matrix after curing of the photocurable adhesive composition is not greater than 0.5 W / m·K.

9. A photoelectric tweezers chip, characterized in that, The photoelectric tweezers chip is prepared by any one of claims 1 to 8, comprising: The upper electrode includes a transparent substrate, a transparent conductive layer located on one side of the transparent substrate, a patterned metal electrode layer located on the side of the transparent conductive layer away from the transparent substrate, and a dry film microstructure self-aligned with the patterned metal electrode layer; the dry film microstructure includes a sidewall forming a microchannel and an opening region corresponding to the patterned metal electrode layer, wherein at least one edge of the sidewall has a self-aligned positional relationship with the corresponding edge of the patterned metal electrode layer; A lower electrode plate, located on one side of the upper electrode plate, comprising a phototransistor array; and A photocurable adhesive layer is sandwiched between the upper electrode plate and the lower electrode plate, and the photocurable adhesive layer is formed by curing a photocurable adhesive composition in which photothermal responsive components are dispersed; The dry film microstructure and the lower electrode plate form a microchannel for the passage of microfluidic fluid, and the microchannel is connected to the surface of the patterned metal electrode layer through the opening region.

Citation Information

Patent Citations

  • Photoelectric tweezer chip and manufacturing method thereof

    CN120001439A

  • Molecule analyzing method using microchannel

    WO2004010140A1